2013
DOI: 10.1128/jvi.03129-12
|View full text |Cite
|
Sign up to set email alerts
|

Toscana Virus NSs Protein Inhibits the Induction of Type I Interferon by Interacting with RIG-I

Abstract: Toscana virus (TOSV) is a phlebovirus, of the. In this study, we investigated whether an upstream sensor, which has a role in the signaling cascade leading to the production of type I IFN, was involved. We found a significant decrease in RIG-I protein levels in cells overexpressing TOSV NSs, suggesting that the nonstructural protein interacts with RIG-I and targets it for proteasomal degradation. In fact, the MG-132 proteasome inhibitor was able to restore IFN-␤ promoter activation in cells expressing NSs, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…5). When expressed separately from their cognate viruses, both PTV and TOSV NSs proteins act as reasonably potent IFN antagonists (53,54), as also observed for the NSs protein of sandfly fever Sicilian virus (53,55). We observed a 10-fold increase in IFN production when A549 cells were infected with the NSs-deleted viruses, suggesting that UUKV NSs also plays a role in antagonizing the host cell IFN response.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…5). When expressed separately from their cognate viruses, both PTV and TOSV NSs proteins act as reasonably potent IFN antagonists (53,54), as also observed for the NSs protein of sandfly fever Sicilian virus (53,55). We observed a 10-fold increase in IFN production when A549 cells were infected with the NSs-deleted viruses, suggesting that UUKV NSs also plays a role in antagonizing the host cell IFN response.…”
Section: Discussionmentioning
confidence: 50%
“…As UUKV NSs localizes in the cytoplasm (57), like other phlebovirus NSs proteins, its mode of antagonizing the IFN response is expected to be different from that of RVFV. TOSV NSs inhibits the dimerization of IFN regulatory factor 3 (IRF-3), hence preventing its localization to the nucleus and the subsequent induction of the IFN-␤ promoter (52), and this is most likely because the protein inhibits the induction of type I IFN by targeting retinoic acidinducible gene I (RIG-I) for proteasomal degradation (54). In SFTSV-infected cells, NSs forms cytoplasmic structures termed viroplasm (58), which are believed to redistribute RIG-I signaling components in order to suppress IFN responses (49,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…The signal transduction between mitochondrial antiviral signaling protein and TBK1 is mediated by mediator of IRF3 activation (MITA). However, LGP2, lacking the two caspase recruitment domains in the N terminus, is believed to act as a negative regulator of the RLR signaling pathway (3)(4)(5)(6)(7). Recently, several reports demonstrated that a functional RLR signaling pathway also exists in fish, suggesting that the RLRmediated antiviral pathway is conserved from lower vertebrate to mammals (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…28,29,32 We assume that RVFV NSs functions, such as general transcription suppression, PKR degradation, or IFN-b suppression, coordinately support efficient RVFV replication and spread in liver tissues, and thus, the spreads of rZH501-TOSNSs and rZH501-SFSNSs were more restricted than parental rZH501 in mouse livers.…”
Section: Discussionmentioning
confidence: 99%
“…Toscana virus (TOSV), sandfly fever Sicilian virus (SFSV), or Punta Toro virus (PTV) Adames strain (PTA) are known to inhibit the upregulation of IFN-b gene. [28][29][30][31] In addition, TOSV NSs also promotes the degradation of PKR. 32 The MP-12 encoding TOSV NSs (rMP12-TOSNSs), however, showed increased viral encephalitis in vaccinated mice (30% or more), compared to parental MP-12, which causes encephalitis in up to 5% of mice.…”
Section: Introductionmentioning
confidence: 99%